Biliary Self-Expandable Metal Stent Could Be Recommended as a First Treatment Modality for Immediate Refractory Post-Endoscopic Retrograde Cholangiopancreatography Bleeding - Sun Young Moon; Jun Heo; Min Kyu Jung; Chang Min Cho (Korean Society of Gastrointestinal Endoscopy, 2022)
Background/Aims Recent reports suggest that the biliary self-expandable metallic stent (SEMS) is highly effective for maintaining hemostasis when endoscopic hemostasis fails in endoscopic retrograde cholangiopancreatography (ERCP)-related bleeding. We compared whether temporary SEMS offers better efficacy than angioembolization for refractory immediate ERCP-related bleeding. Methods Patients who underwent SEMS placement or underwent angioembolization for bleeding control in refractory immediate ERCP-related bleeding were included in the retrospective analysis. We evaluated the hemostasis success rate, severity of bleeding, change in hemoglobin levels, amount of transfusion, and delay to the start of hemostasis. Results A total of 27 patients with SEMS and 13 patients who underwent angioembolization were enrolled. More transfusions were needed in the angioembolization group (1.0±1.4 units vs. 2.5±2.0 units; p=0.034). SEMS failure was successfully rescued by angioembolization. The partially covered SEMS (n=23, 85.1%) was generally used, and the median stent-indwelling time was 4 days. The mean delay to the start of angioembolization was 95.2±142.9 (range, 9-491) min. Conclusions Temporary SEMS had similar results to those of angioembolization (96.3% vs. 92.3%; p=0.588). Immediate SEMS insertion is considered a bridge treatment modality for immediate refractory ERCP-related bleeding. Angioembolization still has a role as rescue therapy when SEMS does not work effectively.